(untitled) (Research, Society and Development, 2025)
The objective of this study is to contribute to the Portuguese Language and Literature Courses at public and private universities, these courses responsible for a significant part of the training of Basic Education teachers in the state and with society in general, since the work is focused on Textual Linguistics, in an attempt to observe whether what the official documents predict for textual production are being fulfilled. The aim is to understand how curricular proposals related to Text Linguistics are being applied in classrooms. The methodology used is bibliographical research, based on authors such as Marcuschi, Proença Filho and Eni Orlandi, to theoretically support the study. In the final considerations, the study highlights the challenges that still exist, such as the need for continued training for teachers and the contextualization of content in the social environment of schools. However, it is noteworthy that investing in the valorization of Text Linguistics can favor a more meaningful, communicative and liberating education, which stimulates the development of students’ linguistic skills.